Virtuous Anger?: From Questions of - Mattison, William (Journal of the Society of Christian Ethics, 2004)
Can a Christian experience virtuous anger? Anger is most commonly understood as a desire for vindicatio, which is the rectification of injustice. Recent discussions of anger in theological ethics have focused nearly exclusively on the possibility and parameters of Christian vindicatio. While this issue is crucial, attending to it alone neglects equally important questions concerning the moral evaluation of an emotion. Does it make sense to label an emotion such as anger praiseworthy or blameworthy? If so, how does one develop virtuous anger? In this essay, I rely on Thomistic moral theology and contemporary neuropsychology not only to argue that anger is a moral phenomenon, but also to explore how one might progressively develop a disposition to experience good anger.